Technical Assistance for Developing Operational Guidelines for Biofortification of Staple Food Crops - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
The work has been completed, HarvestPlus have provided all inputs. Nutrition International (who is managing the project) will publish the document.